Interest in Learning English: A Study of Junior High School Students in Toraja Utara - Tangkeallo, Grace Aprilia; Korompot, Chairil Anwar; Sofyan, Ryan Rayhana (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
Toraja Utara, a province in Indonesia, aims to create a young generation who can use English as a primary language. Learning is a crucial need for students to enhance their learning. This study aims to understand the factors influencing students' English language learning at SMP Negeri 3 Buntao' Satap, using qualitative research methods such as observation and interviews with students, English teachers, and school principals. The study reveals that the learning environment at SMP Negeri 3 Buntao Satap is poor due to internal factors such as physical challenges, students' understanding, attitude, and boredom, external factors like family environment, teaching methods, facilities, and learning resources, and non-social factors like the school's distance from the effort to help students learn English in formal education.